Water : conservation, use, and management for semi-arid region - Nagarajan, R. (New Delhi : Capital Pub. Co., 2006)
Chiefly with reference to India
Includes bibliographical references and index
Keywords: Arid regions -- Water-supply -- Management; Water harvesting; Water use; Water quality management